Reflections about the regional monograph of Slovenia - Drozg Vladimir; Albrecht Volker (Journal for Geography, 2007)
This contribution shows editors’ reflections on the scheme and the contents of the regional geographical monograph of Slovenia. The question is exposed on the concept of the regional geographical survey, interpretation methods, cartographic showings, national context and usage of scientific tools.